Regarding a Trialist Theory of Conciliation - Rincón, Ariel (DIXI, 2014)
The study of law is a complete picture of facts, norms and values. Conciliation is composed of sociological, rule-based and axiological elements. Th creation of norms for conciliation must fi into this dynamic, otherwise it frequently leads to distance between norms and social reality. Ths article is the result of research completed as part of the Masters Program in Thory and Practice of Legal Rulemaking, entitled “A Trialist Thory of Conciliation,” which was directed by Professor Miguel Angel Ciuro Caldani.